Recycling steel slag as substitute for natural aggregate in construction: dual benefits for GHG emission reduction and environmental protection in Vietnam - Duong, Trung Quoc; Tran, Thanh Nhan; Tran, Thi Ngoc Quynh; Nguyen, Thi Le Huyen; Do, Quang Thien; Tran, Xuan Thach; Nguyen, Thanh Hai; Nguyen, Huu Dong (Hue University Journal of Science: Natural Science, 2025)
In Vietnam, the annual production of steel slag, a byproduct of the steel-making process, has exceeded 3 million tons since 2018. Due to its advantageous properties, over 85% of steel slag is recycled and utilised in construction in developed countries. However, in Vietnam, a significant portion remains either stockpiled at steel plants or used as backfill material, posing risks of soil and water pollution. Meanwhile, natural construction materials such as river sand are becoming depleted, and the extraction of resources like crushed stone leads to various environmental issues. Therefore, recycling steel slag as a substitute for natural construction materials not only mitigates environmental pollution associated with the steel industry but also reduces the depletion of natural resources, contributing to energy conservation and lower greenhouse gas emissions in the construction sector. This study presents initial findings on the use of steel slag as an aggregate in concrete for coastal protection structures, such as wave-breaking blocks, which are essential as coastal erosion has become a critical issue in numerous areas of Vietnam.